Fluorescence and Treatment Light Monitoring for Interstitial Photodynamic Therapy. (13th February 2020) - Heckl, Christian; Aumiller, Maximilian; Rühm, Adrian; Sroka, Ronald; Stepp, Herbert
Abstract: In interstitial photodynamic therapy, light is distributed to the tumor via light diffusers. The light dose and the related phototoxic effect achieved throughout the target volume critically depend on absorption, scattering and diffuser positioning. Using liquid tissue phantoms, we investigated the dependencies of treatment light transmission and protoporphyrin IX (PpIX) fluorescence on these parameters. This enabled monitoring hemoglobin oxygenation and methemoglobin formation during irradiation (635 nm, 200 mW cm −1 diffuser length). Starting with two parallel cylindrical diffusers at 10 mm radial separation, the light transmitted between the fibers was largely determined by the minimal distance between the diffusers, but rather insensitive to an additional axial displacement or tilting of one fiber with respect to the other. For fixed distance between the diffusor centers, however, tilting up to direct contact resulted in a 10‐fold signal increase. For hemoglobin within erythrocytes, irradiation leads to photobleaching of PpIX without marked change in hemoglobin oxygenation until hemolysis occurs. Afterward, hemoglobin is rapidly deoxygenized and methemoglobin is formed, leading to a dramatic increase in absorption. For lysed blood, these effects start immediately. A comparison of intraoperative monitoring of the signals with the experimental results might help prevent insufficient treatment by reconsidering treatment planning or prolonging irradiation. Abstract : In interstitial photodynamic therapy (iPDT), transmitted treatment light monitoring showed a reduction in intensity during illumination. In experiments, using optical phantoms containing lysed blood as an absorber, transmission spectra were recorded during illumination (635 nm, 200 mW cm −1 ) with cylindrical diffusers. Spectral analysis with regard to pure spectra of oxygenated, deoxygenated and met‐hemoglobin showed a time‐dependent increase of deoxy‐hemoglobin with a maximum at 40 min at the cost of oxy‐hemoglobin, while met‐hemoglobin is continuously formed. This effect may explain the observed clinical data and should be taken into account for iPDT dosimetry concepts.